The political ideology of Islam as expounded by Imam Al-Mawardi and its practical implementation in Indonesia - Ramadhan, Farhan Arif; Maulia, Shepti; Al Alif, Muamar Zahwa; Salsabila, Fatikha; Faiza, Atika Nur (Green Publisher Indonesia, 2025)
This study explores the political ideology of Imam al-Mawardi as presented in